The impact of insufficient promotion and unattractive packaging towards brand (case study : buncho) / Nurrul Shahirah Mohd Zain - Mohd Zain, Nurrul Shahirah (Faculty of Art and Design, 2013)
This chapter will describe the whole process of this project, started from the main introduction of the Bunchos’ product until its solution. The problem of this product is due to its lack of attention on promoting and redesigning eye-catching packages which may attract customers to purchase it. This whole process consists of four stages which are Literature review, Objectives and research methodology, Analysis and findings, and Proposal. Each and every stage has its own purpose and contents. Basically, literature review focuses on the impact of Buncho coloring product which have reduce in number of demands in the local market, whereby a few researches are made to this products and compares with its competitor. Theoretical study is conducted through references from internet, textbooks, and even written materials such as books and newspapers. A numbers of approaches have been made not only between competitors but in other potential items as well in order to cater the problem. Early reviews are also conducted in this stage to identify problems and any information obtained will be used as a reference to provide a form of observation. The main focus of objectives and research methodology is to promote a new design that will attract more customers on knowing the Buncho coloring materials and significantly increase the market demand. The methodology stated will be the procedure of the project execution as a solution in order to cater the problem.